Introduction of an abbreviated breast MRI service in the UK as part of the BRAID trial: practicalities, challenges, and future directions. Issue 6 (June 2021) - Vinnicombe, S.; Harvey, H.; Healy, N.A.; Papalouka, V.; Schiller, A.; Moyle, P.; Kilburn-Toppin, F.; Allajbeu, I.; Sharma, N.; Maxwell, A.J.; Payne, N.; Graves, M.; et al.
Highlights: BRAID (Breast Screening - Risk Adaptive Imaging for Density). BRAID is a randomised, multi-centre UK study of supplemental breast imaging. Abbreviated Breast MRI is feasible in the UK and can be undertaken in <8 minutes. Dedicated MRI sessions with standard contrast dose improves efficiency.